Exploration and prevalence of gastrointestinal worm in buffalo from West Java, Central Java, East Java and Lombok, Indonesia - Wahyudin Abd. Karim; Achmad Farajallah; Bambang Suryobroto (Aceh Journal of Animal Science, 2016)
The studies of parasites in buffaloes have not been widely explored. The aim of the present study was to explore the prevalence of gastrointestinal worm infection in buffaloes. The fresh faecal samples were collected from 89 buffaloes and observed by a modified McMaster technique. The faecal of buffaloes were collected in Bogor, Demak, East Java, and Lombok. The results of identification on gastrointestinal parasites show that there were one cestode and eight nematode. The total prevalence and infestation of cestodes and nematodes was found highest in Bogor. The prevalence and infestation of differences in geographical conditions were found highest in Bogor. The prevalence of gastrointestinal worm in males were highest than female, whereas for larger was found in females. The prevalence of gastrointestinal worms was found at age 1 year, whereas a larger infestation was found at the age of 1-5 years. The calculation of FEC in Bogor was 840 EPG, in Demak 375 EPG, in East Java 570 EPG and in Lombok 13 EPG. This study informed that there were nine genera of gastrointestinal worm found in Java and five genera in Lombok. Types larvae were found six i.e Strongyloides, Haemonchus, Cooperia, Oesophagostomum, Bunostomum and free living larvae.